Loneliness is associated with the subjective evaluation of but not daily dynamics in partner relationships - Mund, Marcus; Weidmann, Rebekka; Wrzus, Cornelia; Johnson, Matthew D.; Bühler, Janina Larissa; Burriss, Robert Philip; Wünsche, Jenna; Grob, Alexander (International journal of behavioral development, 2022)
Loneliness describes a perceived deficiency in quantitative or qualitative aspects of individuals’ social relationships. Whereas the health-related consequences of loneliness are well-documented, surprisingly little is known about its interpersonal features and its consequences for relationship outcomes. In the present study, we investigated the association between loneliness and relationship experiences in partner relationships with a sample of 937 individuals from 480 mixed-sex couples. By employing actor-partner interdependence models and dyadic cross-lagged moderated multilevel models, we found higher loneliness to be robustly related to (a) lower relationship satisfaction for both oneself and the partner, (b) more self-reported, but not partner-reported conflicts, (c) lower average levels of one’s own, but not the partner’s closeness, and (d) less own self-disclosure. In contrast, loneliness was not associated with (a) sexual contact frequency, (b) average levels of physical affection, or (c) the daily dynamics between closeness and self-disclosure/physical affection. Thus, the results of the present study indicated that loneliness is primarily associated with the perception of the partner relationship but not its rather objective features or daily dynamics.